Innovative language learning/teaching process in higher education institutions. A Polish-Lithuanian comparative study = Innowacyjne nauczanie/uczenie się języka obcego w szkole wyższej. Polsko-litewskie badanie porównawcze - Karczewska, Małgorzata; Žeguniene, Vaida; Kupriene, Laima (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article reviews innovative educational technologies. A theoretical review of innovative teaching/learning methods is then juxtaposed with Polish and Lithuanian higher education reality. The aim of the survey was to find out what modern technologies are used in foreign language teaching and what modern technologies the respondents would like to have used in the foreign language classroom, and why. 100 Polish and 100 Lithuanian university students were asked to fill in a questionnaire. As digital natives, the respondents were expected to be familiar with modern technologies and willing to use them in foreign language learning.
Keywords: educational technologies; foreign language education; innovative teaching; learning methods; innowacyjne metody nauczania; nauczanie języka obcego; technologie edukacyjne